The influence of erosion and wear on the accretion and adhesion of ice for nano reinforced polymetric composites used in aeronautics - Gohardani, Omid (Cranfield University, 2011)
The usage of polymeric matrix composites in aerospace applications has been significantly prevalent based on their desired material characteristics, which include higher strength, lower weight and heat resistance. With current advancements in nanotechnology, carbon nanotube reinforced polymeric matrix composites may enhance the operational usage of these advanced materials even further. In this study, a set of novel aerospace material candidates are characterized based on their mechanical properties, resilience to liquid erosion, wettability and ice adhesion. The experimental evaluations presented, allow for a preliminary ranking of the polymeric matrix composites and assessment of the influence of reinforcing carbon nanotubes. The role of erosion in particular is highlighted from both a historical viewpoint and based on empirical results for static and dynamic wettability and ice adhesion. Discussion of different ranking systems and fractography arising as a consequence of liquid impact are further addressed in this study. It is found that the candidate samples exhibit different physical parameters but nominally similar erosion resilience despite the presence of the reinforcing carbon nanotubes. The wettability of the experimental materials and their ice adhesion characteristics are further shown to be influenced by the presence of carbon nanotubes and largely dependent upon degradation of the material surfaces.